Allelopathic effect of Brassica on weed control and yield of wheat - Biswas, PK; Morshed, MM; Ullah, MJ; Irin, IJ (Bangladesh Agronomy Journal, 2015)
The experiment was conducted at the Agronomy farm of Sher-e-Bangla Agricultural University to identify the allelopathic effect of Brassica species along with their incorporation methods to control weeds in wheat field. The experiment was assigned in a split-plot design where three cultivated Brassica spp. were in the main plot and five different ways of green Brassica biomass inclusion were in the sub-plot. Brassica crops were uprooted at 30 days after sowing (DAS) and incorporated to the soil @ 0.5 kg m-2 as per treatment. Wheat seeds were sown on December 04, 2007 using 20 cm line to line distance. Weeds e.g., Amaranthus spinosus, A. viridis, Lindernia procumbens, Heliotropium indicum, Polygonum hydropiper, Celosis argentina, Ageratum conyzoides, Brassica kaber and Digitaria ischaemum were not found in the wheat field. Significantly the highest weed dry matter (1.72 g m-2) was found in Brassica juncea plots at 30 DAS but in Brassica napus field (1.44 g m-2) at 50 DAS. The lowest weed dry matter at 30 DAS (0.89 g m-2) was recorded with total incorporation of Brassica biomass to the soil but 50% incorporation and 50% spreading at 50 DAS. The Brassica biomass spreading above ground, mixed with soil and 50% spreading + 50% mixed with soil resulted positively compared to other ways of biomass incorporation. The highest grain yield (3.83 t ha-1) of wheat was given by Brassica juncea when spreaded on the above ground soil. Bangladesh Agron. J. 2014, 17(1): 73-80